Peran dan Fungsi Lembaga Penjamin Simpanan Pada Bantuan Likuiditas Yang Dilakukan oleh Bank Century - Muhammad Rafli; Danindra Zachrie; Astri Dewi Setyarini; Dwi Desi Yayi Tarina (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
At that time Century Bank attracted a lot of public attention because it was a bank affected by the monetary crisis, based on Article 1 Number 24 of Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking. What is meant by the Lembaga Penjamin Simpanan (LPS) is a legal entity that carries out guarantee activities for the deposits of deposit customers through insurance schemes, buffer funds, or other schemes. The Lembaga Penjamin Simpanan (LPS) is an independent body tasked with protecting the security of customer funds stored in banks. This research aims to find out what the roles and functions of the Lembaga Penjamin Simpanan (LPS) are, as well as how the Lembaga Penjamin Simpanan (LPS) resolves the Century Bank case. The research method used is normative juridical, where the researcher uses references to books, journals and laws in it. This research found that the Lembaga Penjamin Simpanan (LPS) guarantees and is active in maintaining the banking system in Indonesia, apart from that the Lembaga Penjamin Simpanan (LPS) finally took over 90% of Bank Century and re-branded it as Bank Mutiara.